Impact of Integrated Care Models on Chronic Disease Management Outcomes in Underserved Communities: A Mixed-Methods Study in Surabaya, Indonesia - Sarah Istiqomah; Iting Shofwati; Theresia Putri Sinaga; Lin Chia (HM Publisher, 2025)
Integrated care models (ICMs) are increasingly promoted as a strategy to improve chronic disease management, but evidence of their effectiveness in resource-constrained settings like Surabaya, Indonesia, is limited. This study aimed to evaluate the impact of an ICM on chronic disease management outcomes in underserved communities in Surabaya. A mixed-methods study design was employed, combining a quantitative quasi-experimental component with qualitative data collection. The quantitative component compared pre- and post-intervention data on key clinical indicators (blood pressure control, HbA1c levels, medication adherence) and healthcare utilization (hospital admissions, emergency room visits) for patients with hypertension, diabetes, and cardiovascular disease enrolled in an ICM program (n= 250) versus a control group receiving standard care (n= 250). Data was analyzed using descriptive statistics, t-tests, and chi-square tests. The qualitative component involved semi-structured interviews with patients (n=30) and healthcare providers (n=15) participating in the ICM to explore their experiences and perceptions of the program's impact. Thematic analysis was used to analyze the qualitative data. The quantitative analysis revealed statistically significant improvements in several clinical indicators for the ICM group compared to the control group. Data showed a mean reduction in systolic blood pressure of 8 mmHg (p<0.001) and a decrease in HbA1c levels of 0.7% (p<0.01) in the ICM group. Hospital admissions related to chronic disease complications were also lower in the ICM group (p<0.05). Qualitative findings highlighted improved patient self-management, enhanced provider coordination, and increased patient satisfaction with the ICM. Barriers to implementation included resource constraints, logistical challenges, and the need for ongoing provider training. In conclusion, this study provides evidence that ICMs can improve chronic disease management outcomes in underserved communities in Surabaya, Indonesia. The findings support the scaling up of ICMs in similar settings, with careful consideration of resource allocation, provider training, and community engagement.